HUBUNGAN PEMANFAATAN INTERNET DENGAN PENINGKATAN KAPASITAS PETANI DALAM BERUSAHATANI PADI SAWAH DI DESA LANGGOMEA KECAMATAN UEPAI - Yuaniarti Yuskar; Iskandar Zinuddin Rela; Salahuddin; Dian Agustina (Department of Agricultural Extension, Faculty of Agriculture, Halu Oleo University, 2024)
The dearth of extension workers in this region impedes farmers' access to information, particularly regarding the advancement of innovations in paddy rice farming. Consequently, farmers are increasingly reliant on the internet, yet only a subset of them is able to utilize it to find information pertinent to farming activities. This study aims to ascertain the utilization of the internet and the capacity of wet-rice farmers in Langgoema Village, Uepai Subdistrict, and to examine the relationship between the two. The population under study consisted of all rice farmers in Langgomea Village, Uepai District, Konawe Regency, amounting to 88 individuals. These farmers were grouped into six farmer groups. The sample size was determined using the Slovin formula with an error rate of 10%, resulting in a sample size of 32 rice farmers. Data were collected using survey techniques, interviews, and documentation using questionnaires. This research employed a quantitative approach. The data were subjected to descriptive statistical analysis using the class interval formula and inferential statistical analysis using the Spearman rank correlation formula. The research findings indicate that the Internet utilization of wetland rice farmers is in the medium category. This can be observed in the Internet utilization indicators, which include information, relationships, and sustainability, all of which are in the moderate category. The capacity of rice paddy farmers is in the medium category. Internet utilization based on knowledge, attitudes, and skills are all in the medium category. The utilization of the Internet by wetland rice farmers in Langgomea Village is found to have a very strong and positive relationship with their capacity. It is evident that high levels of Internet utilization contribute to increased capacity.